Pengaruh Latihan Ladder Drill Ickey Shuffle Terhadap Kelincahan Pemain Sepakbola pada Klub Sepakbola Arema Manding 85 FC KU-19 - Majid Aznun Z; Ach. Widodo; Awang Firmansyah; Heri Wahyudi (Journal of Creative Student Research, 2024)
Agility is an effort to move quickly by moving the body without having to lose body balance. Their agility can help athletes maximize their performance in playing. To achieve good agility results, you must practice regularly and gradually. The Agility Ladder Drill is a form of exercise to improve overall agility, speed and foot coordination. To achieve maximum results in agility training, there are several exercises that are needed to increase agility.The aim of this research was to determine the effect of ladder drill ickey shuffle training on the agility of football players at the Arema Manding 85 FC KU-19 club. To determine the effect of ladder drill ickey shuffle training on the agility of football players at the Arema Manding 85 FC KU-19 club. This research design uses a one group only pretest posttest design with a sample size of 22 males with an average height of 160.5cm, an average weight of 50kg, an average BMI of 19.4kg/m2 This design is used to see the results of the treatment. There is a difference between before (pre test) and after treatment (post test) Ladder Drill ickey Shuffle on the agility of Arema Manding 85 FC KU-19 club soccer players as evidenced by t count > t table (10.044 > 2.080) which means Ha is accepted and H0 is rejected . There is an increase in the influence of the Ladder Drill ickey Shuffle treatment on the agility of Arema Manding 85 FC KU-19 club football players as evidenced by the calculation results of 20.7%